Variable clinical expression of a Belgian TGFB3 founder variant suggests the presence of a genetic modifier - Perik, Melanie H. A. M.; Govaerts, Emmanuela; Laga, Steven; Goovaerts, Inge; Saenen, Johan; Van Craenenbroeck, Emeline; Meester, Josephina A. N.; Luyckx, Ilse; Rodrigus, Inez; Verstraeten, Aline; Van Laer, Lut; Loeys, Bart L. (Frontiers in Genetics, 2023)
Background: TGFB3 variants cause Loeys-Dietz syndrome type 5, a syndromic form of thoracic aortic aneurysm and dissection. The exact disease phenotype is hard to delineate because of few identified cases and highly variable clinical representation. Methodology: We provide results of an haplotype analysis as well as a medical record review of clinical features of 27 individuals from five different families, originating from the Campine region in Flanders, carrying the NM_003239.5(TGFB3):c.787G>C p.(Asp263His) likely pathogenic variant, dbSNP:rs796051886, ClinVar:203492. The Asp263 residue is essential for integrin binding to the Arg-Gly-Asp (RGD) motif of the TGFβ3-cytokine. Results: Haplotype analysis revealed a shared haplotype of minimum 1.92Mb and maximum 4.14Mb, suggesting a common founder originating >400 years ago. Variable clinical features include connective tissue manifestations, non-aneurysmal cardiovascular problems such as hypertrophic cardiomyopathy, bicuspid aortic valve, mitral valve disease and septal defects. Remarkably, only in 4 out of 27 variant-harboring individuals, significant aortic involvement was observed. In one family, a 31yr old male presented with type A dissection. In another family, the male proband (65yrs) underwent a Bentall procedure because of bicuspid aortic valve insufficiency 2 combined with a sinus of Valsalva of 50mm, while an 80yr old male relative had an aortic diameter of 43mm. In a third family, the father of the proband (75yrs) presented with an ascending aortic aneurysm (44mm). Conclusion: The low penetrance (15%) of aortic aneurysm/dissection suggests that haploinsufficiency alone by the TGFB3 variant may not result in aneurysm development but that additional factors are needed to provoke the aneurysm phenotype.